2019
DOI: 10.1007/s12195-019-00582-3
|View full text |Cite
|
Sign up to set email alerts
|

Coencapsulation of ISCs and MSCs Enhances Viability and Function of both Cell Types for Improved Wound Healing

Abstract: IntroductionWe previously demonstrated that insulin secreting cells (ISCs) accelerate healing of chronic wounds, and it is known that mesenchymal stem cells (MSCs) also accelerate wound healing. Here, we report that the combination of both cell types coencapsulated into a synthetic hydrogel dressing accelerates chronic wound healing 3 × faster than control and 2 × faster than each cell type delivered singly. Specifically, insulin released by ISCs activates the PI3/Akt pathway, which is vital to the function an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…33,34 The ability of MSCs to enhance wound healing has been highlighted in existing literature. 35 Hence, we hypothesized that the transfer of Our initial observations revealed that miR-27b was poorly expressed in the cutaneous wounds of mice with low healing ability. A previous study reported that miR-27b is down-regulated in burned skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The ability of MSCs to enhance wound healing has been highlighted in existing literature. 35 Hence, we hypothesized that the transfer of Our initial observations revealed that miR-27b was poorly expressed in the cutaneous wounds of mice with low healing ability. A previous study reported that miR-27b is down-regulated in burned skin.…”
Section: Discussionmentioning
confidence: 99%
“…Unfavourable wound healing poses a significant threat to public health with an urgent need for fresh novel targets aimed at managing and treating the complications of unfavourable wound healing outcomes 33,34 . The ability of MSCs to enhance wound healing has been highlighted in existing literature 35 . Hence, we hypothesized that the transfer of miR‐27b by MSC‐derived EVs could play a critical role in cutaneous wound healing via the regulation of downstream factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, an enhanced influence on the neovascularization of diabetes wounds was seen, and the epidermis of the cured diabetic lesion was revealed to be thicker as well as more discriminated than the epidermis of the diabetic lesion that had received no therapy 221 . An additional investigation found that using a PEGDA hydrogel to encapsulate a combination of human BM‐MSCs and rat insulin‐secreting cells enhanced diabetic wound repair approximately three times quicker than in the control groups 222 …”
Section: Biomaterials As Msc Delivery Systemsmentioning
confidence: 70%
“…The results showed that both cell delivery methods improved wound healing rate, with a significant difference observed from 7–9 days after treatment, and the cells delivered by the hydrogel group showed similar healing kinetics compared to the direct injection group [ 72 ]. Another study reported that encapsulating a mixture of human BM-MSCs and rat insulin secreting cells (ISCs) in a PEGDA hydrogel promoted diabetic wound healing almost 3 times faster than control group (14 vs. ~ 40 days), without intermediate scab or scar, through increased secretion of insulin, VEGF, TGF-β1 and the viability and function of MSC improved due to activation of the PI3K-Akt/PKB pathway [ 73 ]. This observation suggests that a combination of different cell types may further enhance the therapeutic effects in the diabetic wound.…”
Section: Hydrogel Scaffolds For Msc Delivery In Diabetic Modelsmentioning
confidence: 99%